An Analysis of The Hospital Bylaws Policies to Protect Healthcare Workers Against Indictments of Adverse Events - Leana, Ade; Bachtiar, Adang (Journal of Indonesian Health Policy and Administration, 2017)
One of the functions of hospital bylaws are a means to provide legal protection for all all parties that are related to the hospital. Legal protection is essential for prosecuted hospital staff members. One of the reasons for indictments is adverse events. The goal of this research is to discover how the hospital by-laws protects the hospital staff in the event of an indictment based on an adverse event and how the by-laws adhere to the guidelines in a comprehensive way. The research design used the qualitative method. The results of this research indicates that the hospital by-laws of RSKO Jakarta, although it has served as a protective method, it still needs further technical-operational policies as a supplement, and there are still discrepancies compared to the guidelines. We suggest that the by-laws of RSKO Jakarta are amended to adhere to the governmental guidelines and to establish supplementing technical-operational policies.